Transcriptome analysis of Drosophila melanogaster laboratory strains of different geographical origin after long-term laboratory maintenance. - Zarubin, M.; Yakhnenko, A.; Kravchenko, E. (Ecology and evolution, 2020)
Positive selection may be the main factor of the between-population divergence in gene expression. Expression profiles of two Drosophila melanogaster laboratory strains of different geographical origin and long-term laboratory maintenance were analyzed using microchip arrays encompassing probes for 18,500 transcripts. The Russian strain D18 and the North American strain Canton-S were compared. A set of 223 known or putative genes demonstrated significant changes in expression levels between these strains. Differentially expressed genes (DEG) were enriched in response to DDT (p = .0014), proteolysis (p = 2.285E-5), transmembrane transport (p = 1.03E-4), carbohydrate metabolic process (p = .0317), protein homotetramerization (p = .0444), and antibacterial humoral response (p = 425E-4). The expression in subset of genes from different categories was verified by qRT-PCR. Analysis of transcript abundance between Canton-S and D18 strains allowed to select several genes to estimate their participation in latitude adaptation. Expression of selected genes was analyzed in five D. melanogaster lines of different geographic origins by qRT-PCR, and we found two candidate genes that may be associated with latitude adaptation in adult flies-smp-30 and Cda9. Quite possible that several alleles of these genes may be important for insect survival in the environments of global warming. It is interesting that the number of genes involved in local adaptation demonstrates expression level appropriate to their geographical origin even after decades of laboratory maintenance.